Applications of Three-Dimensional Printing in the Management of Complex Aortic Diseases - Magagna, Paolo; Xodo, Andrea; Menegolo, Mirko; Campana, Carlo; Ghiotto, Luciano; Salvador, Loris; Grego, Franco (AORTA, 2022)
The use of three-dimensional (3D) printing is gaining considerable success in many medical fields, including surgery; however, the spread of this innovation in cardiac and vascular surgery is still limited. This article reports our pilot experience with this technology, applied as an additional tool for 20 patients treated for complex vascular or cardiac surgical diseases. We have analyzed the feasibility of a “3D printing and aortic diseases project,” which helps to obtain a more complete approach to these conditions. 3D models have been used as a resource to improve preoperative planning and simulation, both for open and endovascular procedures; furthermore, real 3D aortic models were used to develop doctor–patients communication, allowing better knowledge and awareness of their disease and of the planned surgical procedure. A 3D printing project seems feasible and applicable as an adjunctive tool in the diagnostic–therapeutic path of complex aortic diseases, with the need for future studies to verify the results.
Keywords: 3D Printing; 3D-printed models; aortic diseases; surgical training; preoperative planning